ASSOCIATION OF TREE COMMUNITIES WITH SOIL PROPERTIES IN A SEMI DECIDUOUS FOREST OF PERLIS, PENINSULAR MALAYSIA - Radhiah Zakaria; Mohd Nizam Mohd Said; Faridah Hanum Ibrahim (Biotropia: The Southeast Asian Journal of Tropical Biology, 2019)
Plant community distribution is associated with environmental factors, particularly, the soil properties of habitats. This study was conducted to determine the effect of soil properties on the association of tree communities within three distinct habitats in a semi-deciduous forest in Perlis State Park (PSP), Perlis.  Eighteen plots of 40 m × 60 m (0.24 ha each) with sampling areas of 1.92 ha (8 plots) in Setul Formation, 0.96 ha (4 plots) in Granite and 1.44 ha (6 plots) in Kubang Pasu Formation (totalling 4.32 ha) were established at the PSP. All trees with 5.0 cm and above diameter at breast height (dbh) were enumerated, while the top soil samples were collected from each plot for soil analyses. A total of 412 tree species, 207 genera, and 68 families were recorded; 270 tree species from 152 genera and 57 families in the Setul forest; 204 tree species of 130 genera and 50 families in the Granite forest; and 109 tree species from 76 genera and 31 families in the Kubang Pasu forest. Euphorbiaceae was the most represented family at Setul, Granite and Kubang Pasu with 36, 19 and 12 species, respectively. Soil properties significantly varied among the study sites.  Setul had loam, Kubang Pasu had clay-loam, and Granite had the sandy-loam texture.  The soils were acidic, and had low to high concentrations of available nutrients. Ordinations using canonical correspondence analysis indicated that the soil factors play an important role in the distribution and diversity of plants in these forest habitats.